Eksplorasi Pengalaman Siswa dalam Pembelajaran PAI Berbasis Media Audio Visual - Awwaliyah, Nasywa Safira; Hafidz (Institut Agama Islam Daruttaqwa Gresik, 2024)
The purpose of this study is to understand students' experiences with the audiovisual-based Islamic Religious Education (PAI) curriculum at SMK Muhammadiyah 1 Sragen. Educational media plays an important role in the learning process as it can attract students' attention and increase their participation. In this era of rapidly advancing technology, students are encouraged to be creative and innovative in choosing the right teaching methods and media to improve their learning outcomes. The findings of this study show that the use of audiovisual materials in PAI learning helps create an engaging and interactive learning environment. Unlike conventional methods that tend to be monotonous, students who consistently attend classes using this media are more focused and have better comprehension. Additionally, the use of PowerPoint presentations and videos provided by the instructor helps students understand the material. However, there are still certain challenges in the use of educational media, such as limited time for learning, difficulty in finding the right media models, and costs. Therefore, it is important for students to understand the lesson plan (RPP) and choose the appropriate media so that the learning process can run smoothly and effectively. In summary, this study highlights the importance of using audiovisual materials in PAI instruction to improve student motivation and learning outcomes and offers recommendations to students on how to better utilize media in the teaching process. This study provides important implications for the development of curricula and teaching methods in schools. The use of audiovisual media in PAI learning can be an effective alternative to increase student engagement, especially in creating a more interactive and enjoyable learning experience. Therefore, it is essential for teachers to further develop their ability to effectively utilize technology media, as well as to provide training for students to maximize the use of such media. Furthermore, schools need to consider allocating a larger budget for providing adequate learning media and allowing time for preparing materials that align with the curriculum.